Molecular epidemiological characteristics of Brucella in Guizhou Province, China, from 2009 to 2021 - Tan, Qinqin; Wang, Yue; Liu, Ying; Tao, Zhongfa; Yu, Chun; Huang, Yan; Yang, Xinggui; Ying, Xia; Hu, Yong; Li, Shijun (Frontiers in Microbiology, 2023)
Brucellosis was made statutorily notifiable in 1955, in China, but it has only been reported in Guizhou since 2009. Here, we analyzed the epidemiological characteristics of a total of 559 human brucellosis cases and the molecular characteristics of 83 Brucella in Guizhou from 2009 to 2021. Among the 83 Brucella, MLST identified three ST genotypes, of which ST39 is a newly reported type in China. MLVA-16 generated 49 genotypes and MLVA-11 generated 5 known genotypes and 2 unreported genotypes. Six genotypes were identified by rpoB technology. MLST and rpoB genotype techniques are consistent with the analysis of Brucella population structure and evolutionary relationships. MLVA has a high resolution, but the difference at loci bruce 04 and 16 cannot exclude an association between epidemics, so combing MLST and rpoB typing methods for epidemiological traceability analysis is essential. In addition, the origin of the new genotype of Brucella can be reasonably inferred by MLST and rpoB techniques.